Comparisons of 304 austenitic stainless steel manufactured by laser metal deposition and selective laser melting. (September 2020) - Zhang, Yimin; Huang, Weibo
Abstract: Selective laser melting (SLM) and laser metal deposition (LMD) are the two methods of laser additive manufacturing (LAM), which are distinguished by the different powder feeding methods. In this paper, the temperature field (temperature distribution, cooling rate, temperature gradient and dimensions of molten pool), appearance and microstructure (grain shape and size, and phase composition) of the LMDed 304 austenitic stainless steel (SS304) specimen are compared with those of the SLMed SS304 specimen published in the previous literature. The results show that the LMDed SS304 specimen has the similar temperature field trend with the SLMed SS304 specimen. The differences for temperature field obtained by the finite element models (FEMs) are that LMD produces the higher temperature and dimensions of molten pool, but the lower cooling rate and temperature gradient. The appearances of the LMDed and SLMed specimens are compared. Since the molten pool during LMD is larger, the surface roughness of the LMDed SS304 specimen is higher than that of the SLMed SS304 specimen. Due to the different cooling rates, the LMDed SS304 specimen has the different microstructure from the SLMed SS304 specimen. The SLMed and LMDed specimens have the similar columnar grain shape, but the grain size of the LMDed specimen is larger. The microstructure of LMDed SS304 specimen is composed of two phases, which are austenite phase and small amount of ferrite phase. But the SLMed specimen has the full austenite phase. The differences between SLM and LMD are also studied in this paper.